Permanent global crisis, biopolitics, and twenty-first century ethico-political turn - Koljević Grifit, Bogdana (Sociološki pregled, 2024)
In this article, the issue of the permanent global crisis is reflected from the perspective of political theory, geopolitics, and contemporary political philosophy. The author emphasizes how this interdisciplinary approach is necessary for comprehending the existential crisis of the humankind as a manifestation of neoliberalism and postmodernity, i.e., in final instance, as a manifestation of theory and practice of biopolitics. In the relevant sense, it is articulated that what is at stake is precisely the condition of post-truth that functions through the logic of equivalence and then, how one of the exemplary biopolitical phenomena in the 21st century is artificial intelligence (AI). In the second part, the philosophical and practical basis for overcoming biopolitical transhumanism is outlined through the contemporary ethico-political turn. New forms of subjectification are presented as a manifestation of the conceptual interrelation between truth, freedom, and equality as true democracy – and the multipolar world, in its most fundamental determination, appears as the world of de-colonization.
Keywords: permanent global crisis; biopolitics; ethico-political turn; subjectification; multipolarism